Values and Potential of the Elderly in the Northeast - Mina, Chalermkiat (Journal of Graduate MCU KhonKaen Campus, 2022)
This article aims to study the values and potential of the elderly in the Northeastern. Use combined research. Sample of 200 people for quantitative research and 50 people for qualitative research was collected. The sample group was the elderly in the Northeastern region. The researcher took a simple random sampling from 4 provinces, namely Khon Kaen, Kalasin, Mahasarakham and Roi Et. Data were collected using a questionnaire and an in-depth interview form. Analyze the data by finding percentages. The data from the in-depth interviews were analyzed and arranged in order. The findings can be summarized as follows: In terms of values, 54% think they are equal to others; 52% think they are of various qualifications and 62% think they are inferior to others. In terms of competency, 70% think they are equal to others; 52% think they are inferior to others; 68% agree to adopt the concept of self-satisfaction; 66% think they are friendly to all; 54% it is found that the elderly population bear various aspects of competency as follows: 1. Food, 2. Dessert, 3. Bread, 4. Academics, 5. Language. It is recommended that the following activities should be organized for the senior population: 1. Academic service to the public in various fields of expertise where the aged can exercise their knowledge to serve their society. 2. Income-earning activities.